Extraction Optimization, Structural Analysis, and Potential Bioactivities of a Novel Polysaccharide from Sporisorium reilianum - He Shi; Siyi Zhang; Mandi Zhu; Xiaoyan Li; Weiguang Jie; Lianbao Kan (MDPI AG, 2024)
Sporisorium reilianum is an important biotrophic pathogen that causes head smut disease. Polysaccharides extracted from diseased sorghum heads by Sporisorium reilianum exhibit significant medicinal and edible value. However, the structure and biological activities of these novel polysaccharides have not been explored. In this study, a novel polysaccharide (WM-NP'-60) was isolated and purified from the fruit bodies of S. reilianum and aimed to explore the structural characteristics and substantial antioxidant and antitumor properties of WM-NP'-60. Monosaccharide composition determination, periodate oxidation-Smith degradation, 1D/2D-NMR analysis, and methylation analysis revealed that WM-NP'-60 consisted mainly of β-1,6-D-Glcp, β-1,3-D-Glcp, and β-1,3,6-D-Glcp linkages. The antioxidant assays demonstrated that WM-NP'-60 exhibited great activities, including scavenging free radicals, chelating ferrous ions, and eliminating reactive oxygen species (ROS) within cells. The HepG2, SGC7901, and HCT116 cells examined by transmission electron microscopy (TEM) revealed typical apoptotic bodies. Therefore, a novel fungal polysaccharide (WM-NP'-60) was discovered, extracted, and purified in this experiment, with the aim of providing a reference for the development of a new generation of food and nutraceutical products suitable for human consumption.